Intertwining art, religion and anatomy: did Michelangelo Buonarroti influence Berengario da Carpi's representation of a maternal death?. (3rd June 2022) - Lippi, Donatella; Susini, Tommaso; Donell, Simon; Bianucci, Raffaella
Abstract: Aim: To confirm that the sixteenth century surgeon-anatomist, Jacopo Berengario da Carpi, used a woman who died of a ruptured uterus as a model for a woodcut of female genital anatomy, and that the presentation was based on the cloak in Michelangelo's Creation of Adam after visiting the Sistine Chapel in the Vatican whilst he was in Rome. Method: Analysis of the woodcut for evidence of a uterus at term, and comparison with the shape of the cloak in the Creation of Adam, coupled with Berengario's own description. Results: The size of the uterus is that in the 38th to 40th week of pregnancy, further supported by striations of the endometrial surface, rather than the smooth surface of the non-gravid. By rotating the woman's image 90° counterclockwise, the outline of the woman's cloak becomes almost perfectly superimposed over God's cloak. Conclusion: In the woodcut, the open belly of the model shows typical features of the full-term uterus. The use of God's cloak softens the features. At the same time, it exemplifies the creative power of God and describes the birth of humanity in both theological and physiological ways. Intertwining art, religion and anatomy, Michelangelo and Berengario allow scholars to appreciate the concepts of divinity and humanity at multiple levels.